2009
DOI: 10.1287/mksc.1090.0502
|View full text |Cite
|
Sign up to set email alerts
|

“Counting Your Customers” One by One: A Hierarchical Bayes Extension to the Pareto/NBD Model

Abstract: This research extends a Pareto/NBD model of customer-base analysis using a hierarchical Bayesian (HB) framework to suit today's customized marketing. The proposed HB model presumes three tried and tested assumptions of Pareto/NBD models:(1) a Poisson purchase process, (2) a memoryless dropout process (i.e., constant hazard rate), and (3) heterogeneity across customers, while relaxing the independence assumption of the purchase and dropout rates and incorporating customer characteristics as covariates. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 18 publications
3
79
0
8
Order By: Relevance
“…We estimate it in Section 3 by MCMC integration method. As is pointed by Abe (2009), closed-form expressions would provide a better understanding of the effect from each variable. Similar to the experiment conducted in Section 4, we can complement our model by applying logistic regression on the augmented data with default labels predicted in the MCMC iteration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We estimate it in Section 3 by MCMC integration method. As is pointed by Abe (2009), closed-form expressions would provide a better understanding of the effect from each variable. Similar to the experiment conducted in Section 4, we can complement our model by applying logistic regression on the augmented data with default labels predicted in the MCMC iteration.…”
Section: Resultsmentioning
confidence: 99%
“…Our method is similar to that in Abe (2009) which used a hierarchical Bayesian extension of the Prato/NBD model to forecast customers future purchases. Through an empirical analysis on three datasets, they conclude that the customer purchasing behavior is better tracked and, most importantly, the correlation estimated provides significant insights in customer relationship management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach is the NBD/Pareto model (e.g., Schmittlein et al 1987;Reinartz and Kumar 2000). More current studies have reported alternative approaches to measure the inactivity of a customer (Fader et al 2005;abe 2009). The defiance of all approaches is to define adequate defection indicators due to the fact that several repurchase decisions can take years.…”
Section: Management Of Relationship Terminationmentioning
confidence: 99%
“…This model is attracting the attention of researchers and practitioners because of its increasing importance in new types of marketing, such as CRM, and One-to-One Marketing. Their work is highly regarded and follow up research has been conducted [4][5] [6][7] [8]. Abe [8] proposed a hierarchical Bayes extension to the Pareto/NBD model to estimate the impact of the customer's characteristic variables on profitable lifetime duration.…”
Section: Introductionmentioning
confidence: 99%